A preparation method of silver-coated copper powder
By adding crystal form control agents and inhibitors to the preparation process of silver-clad copper powder, the problem of uneven coating is solved and the conductive properties are significantly improved.
Patent Information
- Application Number
- CN202411941196.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
The existing preparation methods for silver-clad copper powder have problems of uneven coating, resulting in poor conductivity.
Silver-covered copper powder is prepared by one-pot method. By adding crystal form control agent to the reduction reaction, the crystal arrangement of copper particles is regulated, and inhibitors and carboxylic acid are added to the reaction liquid to control the replacement reaction speed to achieve uniform coating.
The coating uniformity and particle size of silver-clad copper powder are improved, thereby significantly improving its conductive properties.
Smart Images

Figure BDA0005212603840000101 
Figure HDA0005212603850000011 
Figure HDA0005212603850000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powder preparation, and particularly relates to a method for preparing silver-coated copper powder. Background Art
[0002] Silver powder is the most widely used conductive filler. However, silver reserves are small and the price is high. Silver is prone to silver migration during use and cannot meet the requirements of high-performance electronic components. Copper powder is second only to silver in conductivity. In terms of performance, copper powder is a good substitute for silver powder, but copper powder is easily oxidized, which reduces its conductivity and stability. After the surface of copper powder is coated with metallic silver, the copper powder inside is less in direct contact with the air, thereby significantly improving the antioxidant capacity and overall stability of the copper powder, while reducing production costs.
[0003] At present, most of the silver-coated copper powders are prepared in spherical shape. The contact between spherical particles is point-to-point contact, and the conductivity is usually related to the contact area between particles. Therefore, compared with spherical silver-coated copper powder, polyhedral silver-coated copper powder can effectively improve the conductivity of silver-coated copper slurry because the contact between particles is face-to-face contact.
[0004] For example, patent CN117983808A prepares a polyhedral submicron copper powder suspension, further reduces silver ions in situ on the surface of copper particles, and realizes the preparation of polyhedral silver-coated copper powder. This method is a one-pot preparation, and the process is simple, but the reducing agent easily remains in the copper liquid, causing the silver ion reduction reaction to occur too quickly, and there may be a problem of uneven coating. Patent CN118404056A integrates the preparation of polyhedral copper powder and the coating of copper powder to prepare polyhedral silver-coated copper powder, which is simple to operate, greatly simplifies the process and reduces costs, but the reducing agent may also remain in the copper liquid, causing the silver ion reduction reaction to occur too quickly, which is not conducive to uniform coating. Therefore, it is urgent to improve the preparation method of silver-coated copper powder, improve its coating uniformity, and thus improve its conductive properties. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a method for preparing silver-coated copper powder, which can effectively improve the coating uniformity of the silver-coated copper powder and improve the conductive performance.
[0006] Therefore, in a first aspect of the present invention, the present invention provides a method for preparing a silver-coated copper powder, comprising the following steps:
[0007] Prepare solution A, solution B and solution C; solution A includes copper salt and complexing agent I, solution B includes reducing agent, and solution C includes silver salt, complexing agent I and complexing agent II;
[0008] Solution A and solution B are mixed, and a crystal form control agent is added to perform a reduction reaction to obtain solution D;
[0009] Adding inhibitor and carboxylic acid to solution D;
[0010] Solution C was added dropwise to solution D to carry out a replacement reaction to obtain silver-coated copper powder.
[0011] The present invention adopts a one-pot method to prepare silver-coated copper powder, and adds a crystal form control agent during the reduction reaction process to effectively regulate the crystal arrangement mode of copper during the growth process and regulate the crystal morphology. Subsequently, a replacement reaction of copper replacing silver is carried out. During the reaction process, different complexing agents are used in combination, and inhibitors and carboxylic acids are added to achieve speed control of the replacement reaction, so as to coat a uniform and complete silver layer on the copper substrate. The obtained silver-coated copper powder is polyhedral, has uniform particle size, and is well coated. Therefore, the silver-coated copper powder prepared by the method of the present invention has excellent electrical conductivity.
[0012] In some embodiments, solution A satisfies at least one of the following:
[0013] (A) the copper salt comprises at least one of copper nitrate and copper sulfate;
[0014] (B) Complexing agent I includes at least one of ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid salt, and thiosulfate.
[0015] In some embodiments, solution B satisfies at least one of the following:
[0016] (a) the reducing agent comprises at least one of ascorbic acid, hydrazine hydrate, glucose and potassium sodium tartrate;
[0017] (b) The pH range of solution B is 5-7.
[0018] In some embodiments, solution C satisfies at least one of the following:
[0019] (1) The silver salt includes at least one of silver nitrate and silver sulfate;
[0020] (2) the complexing agent II comprises at least one of ammonium carbonate, ammonium bicarbonate, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and ammonia water;
[0021] (3) The pH range of solution C is 5 to 7.
[0022] In some embodiments, the crystal form control agent satisfies at least one of the following:
[0023] (i) the crystal form controlling agent comprises at least one of ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, and tetraethylene glycol;
[0024] (ii) The molar ratio of the crystal form controlling agent to the copper salt in solution A is (0.01-0.1):1.
[0025] In some embodiments, the molar ratio of the reducing agent in solution B to the copper salt in solution A is (1-2.5):1.
[0026] In some embodiments, the inhibitor and the carboxylic acid are added to the solution D, and at least one of the following is satisfied:
[0027] (I) the inhibitor comprises at least one of imidazole, benzimidazole, thiazole, benzothiazole, 1,2,3-triazole, 1,2,4-triazole, thiadiazole and methylmercaptotetrazole;
[0028] (II) the molar ratio of the inhibitor to the copper salt is (0.005-0.01):1;
[0029] (III) The molar ratio of the inhibitor to the carboxylic acid solution is 1:1.
[0030] In some embodiments, the carboxylic acid includes an organic substance containing a carboxylic acid group.
[0031] In some embodiments, the replacement reaction satisfies at least one of the following:
[0032] (1) The drop rate of solution C is 50-100 mL / min;
[0033] (2) The pH range of solution D is 5 to 7.
[0034] In some embodiments, after the replacement reaction is completed, a drying process is further included; the drying process temperature is 20 to 50° C., and the time is 8 to 12 hours.
[0035] In the second aspect of the present invention, the present invention provides a silver-coated copper powder, including the silver-coated copper powder obtained by the preparation method of the first aspect. Therefore, the silver-coated copper powder of the present invention has excellent conductive properties.
[0036] Compared with the prior art, the present invention has the following beneficial technical effects:
[0037] The present invention adds a crystal form control agent to the reduction reaction of preparing silver-coated copper powder, effectively regulating the crystal arrangement mode of copper during the growth process and regulating the crystal morphology. Inhibitors and carboxylic acids are added to the reaction solution, which can effectively prevent copper oxidation and achieve speed control of the replacement reaction, so that a uniform and complete silver layer is coated on the copper substrate. The prepared silver-coated copper powder is polyhedral and has excellent conductive properties. The preparation method has simple process, low production cost and strong practicality.
[0038] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0040] Figure 1 This is a scanning electron microscope image of the silver-coated copper powder of Example 1 of the present invention;
[0041] Figure 2 This is a scanning electron microscope image of the silver-coated copper powder of Example 2 of the present invention;
[0042] Figure 3 This is a scanning electron microscope image of the silver-coated copper powder of Example 3 of the present invention;
[0043] Figure 4 This is a scanning electron microscope image of the silver-coated copper powder of Example 4 of the present invention;
[0044] Figure 5 This is a scanning electron microscope image of the silver-coated copper powder of Comparative Example 1 of the present invention;
[0045] Figure 6 This is a scanning electron microscope image of the silver-coated copper powder of Comparative Example 2 of the present invention;
[0046] Figure 7 This is a scanning electron microscope image of the silver-coated copper powder of Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0047] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0048] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0049] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0050] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0051] In a first aspect of an embodiment of the present invention, the present invention provides a method for preparing silver-coated copper powder, comprising the following steps:
[0052] Solution A, solution B and solution C are prepared; solution A includes copper salt and complexing agent I, solution B includes reducing agent, and solution C includes silver salt, complexing agent I and complexing agent II;
[0053] Solution A and solution B are mixed, and a crystal form control agent is added to perform a reduction reaction to obtain solution D;
[0054] Adding inhibitor and carboxylic acid to solution D;
[0055] Solution C was added dropwise to solution D to carry out a replacement reaction to obtain silver-coated copper powder.
[0056] According to an embodiment of the present invention, in solution A, after the complexing agent and copper ions undergo a complexing reaction to form a stable complex, the concentration of free copper ions in the solution decreases, which can slow down the reaction rate of copper ions in the subsequent reduction reaction, thereby effectively regulating the size of the generated copper particles. In solution C, the silver ions in the silver salt undergo a complexing reaction with the complexing agent, which can slow down the reaction rate of the subsequent replacement reaction, which is beneficial to improving the uniformity of particle coating.
[0057] Solution A and solution B are mixed, that is, the reducing agent reduces the complex copper, and the reaction rate is slow, which is conducive to controlling the reaction process. A crystal form control agent is further added to the reaction solution. The crystal form control agent mainly plays a capping role and can modify the crystal surface in a directional manner. The crystal form control agent molecules are adsorbed on different crystal surfaces of the copper crystal to produce a certain steric hindrance and affect the exchange rate of the ligand ions, resulting in different growth rates of different crystal surfaces, thereby obtaining polyhedral copper particles.
[0058] Inhibitors and carboxylic acids are added to solution D containing copper particles. The inhibitors and carboxylic acids are mainly adsorbed on the surface of the copper particles to prevent copper oxidation.
[0059] Finally, solution C is added in a titration manner, and the silver ions are allowed to react with the surface of the copper powder in sufficient time by the titration method, so that the silver layer can be evenly deposited on the surface of the copper powder, which helps to form a dense and continuous silver coating layer and improve the conductivity and oxidation resistance of the silver-coated copper powder. After the reaction is completed, a polyhedral silver-coated copper powder is obtained.
[0060] Therefore, the preparation method of the present invention can effectively improve the coating uniformity and particle size consistency of the silver-coated copper powder, thereby improving the conductive performance.
[0061] In some embodiments of the present invention, solution A satisfies at least one of the following:
[0062] (A) the copper salt comprises at least one of copper nitrate and copper sulfate;
[0063] (B) Complexing agent I includes at least one of ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid salt, and thiosulfate.
[0064] In some embodiments of the present invention, the molar ratio of complexing agent I to copper salt is (0.1-0.5):1.
[0065] As an example, the molar ratio is 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, etc.
[0066] In some embodiments of the present invention, solution B satisfies at least one of the following:
[0067] (a) the reducing agent comprises at least one of ascorbic acid, hydrazine hydrate, glucose and potassium sodium tartrate;
[0068] (b) The pH range of solution B is 5-7.
[0069] According to an embodiment of the present invention, solution B is an acidic solution, and the acidic environment can reduce the reducing ability of the reducing agent, thereby slowing down the reduction speed, which is beneficial to controlling the size of copper particles. Therefore, the preparation method of the present invention can effectively improve the consistency of the size of the silver-coated copper powder particles and further improve its conductive properties.
[0070] In some embodiments of the present invention, solution C satisfies at least one of the following:
[0071] (1) The silver salt includes at least one of silver nitrate and silver sulfate;
[0072] (2) the complexing agent II comprises at least one of ammonium carbonate, ammonium bicarbonate, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and ammonia water;
[0073] (3) The pH range of solution C is 5 to 7.
[0074] According to an embodiment of the present invention, the two complexing agents in solution C play a synergistic role and jointly regulate the reduction rate of silver ions. The two complexing agents in solution C have different complexing abilities, complexing agent I has a stronger ability, and complexing agent II has a weaker ability. After the two complexing agents are complexed with silver, the complexing agent II with weak complexing ability first releases silver ions to react with copper, and the complexing agent I with strong complexing ability later releases silver ions to react with copper, thereby achieving a staged reaction and controlling the reaction rate; the pH range of solution C is 5 to 7, mainly to keep the pH of solution C consistent with that of solution D. Therefore, the preparation method of the present invention can effectively improve the coating uniformity of silver-coated copper powder, thereby improving its conductive properties.
[0075] In some embodiments of the present invention, solution C further satisfies at least one of the following:
[0076] (1) The molar ratio of complexing agent I to silver salt is (2-5):1;
[0077] (2) The molar ratio of complexing agent II to silver salt is (4-8):1.
[0078] As an example, the molar ratio of complexing agent I to silver salt is 2:1, 3:1, 4:1, 5:1, etc.
[0079] As an example, the molar ratio of complexing agent II to silver salt is 4:1, 5:1, 6:1, 7:1, 8:1, etc.
[0080] In some embodiments of the present invention, the crystal form controlling agent satisfies at least one of the following:
[0081] (i) the crystal form controlling agent comprises at least one of ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, and tetraethylene glycol;
[0082] (ii) The molar ratio of the crystal form controlling agent to the copper salt in solution A is (0.01-0.1):1.
[0083] As an example, the molar ratio is 0.01:1, 0.02:1, 0.04:1, 0.06:1, 0.08:1, 0.1:1, etc.
[0084] In some embodiments of the present invention, the inhibitor and the carboxylic acid solution are added to the solution D, and at least one of the following is satisfied:
[0085] (I) the inhibitor comprises at least one of imidazole, benzimidazole, thiazole, benzothiazole, 1,2,3-triazole, 1,2,4-triazole, thiadiazole and methylmercaptotetrazole;
[0086] (II) the molar ratio of the inhibitor to the copper salt is (0.005-0.01):1;
[0087] (III) The molar ratio of the inhibitor to the carboxylic acid solution is 1:1.
[0088] According to an embodiment of the present invention, the inhibitor can slow down the oxidation reaction of copper particles in the solution, thereby maintaining the chemical stability of the copper particles and preventing them from being oxidized into copper oxides; carboxylic acid, as an acidic substance, will react with the alkaline substance in the solution after being added, lowering the pH value of the solution, which helps to change the chemical properties of the surface of the copper particles and make them more stable. In addition, the carboxylic acid molecules can be adsorbed on the surface of the copper particles, changing their surface properties and enhancing the dispersibility and stability of the copper particles in the solution. As a result, the present invention can further improve the coating uniformity and particle size consistency of the silver-coated copper powder, thereby improving its conductive properties.
[0089] As an example, the molar ratio of the inhibitor to the copper salt is 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.01:1, etc.
[0090] In some embodiments of the present invention, the carboxylic acid includes an organic substance containing a carboxylic acid group.
[0091] As an example, the carboxylic acid includes at least one of oleic acid and stearic acid.
[0092] In some embodiments of the present invention, the molar ratio of the reducing agent in solution B to the copper salt in solution A is (1-2.5):1.
[0093] As an example, the molar ratio is 1:1, 1.5:1, 2:1, 2.4:1, 2.5:1, etc.
[0094] In some embodiments of the invention, the replacement reaction satisfies at least one of the following:
[0095] (1) The drop rate of solution C is 50-100 mL / min;
[0096] (2) The pH range of solution D is 5 to 7.
[0097] The dripping speed of solution C into solution D is controlled to be 50-100 mL / min, which can prolong the contact time between the silver solution and the copper particles, slow down the replacement reaction rate, and make the silver slowly grow to the surface of the copper particles, which is conducive to improving the uniformity of the coating. Solution D is acidic, which helps the activation and deposition of silver ions on the surface of the copper powder under acidic conditions to form a firm silver coating layer. Therefore, the present invention can effectively improve the coating uniformity of the silver-coated copper powder and further improve its conductive performance.
[0098] In some embodiments of the present invention, the molar ratio of the copper salt in solution D to the silver salt in solution C is (0.2-1):1.
[0099] In some embodiments of the present invention, the pH adjuster includes at least one of sulfuric acid, nitric acid, and sodium hydroxide.
[0100] In some embodiments of the present invention, after the replacement reaction is completed, a drying process is further included; the drying process temperature is 20 to 50° C. and the time is 8 to 12 hours.
[0101] The moisture in the silver-coated copper powder is evaporated by the drying process to obtain a stable silver-coated copper powder.
[0102] In a second aspect of the embodiments of the present invention, the present invention provides a silver-coated copper powder, including the silver-coated copper powder obtained by the preparation method of the first aspect.
[0103] Therefore, the silver-coated copper powder of the present invention has excellent electrical conductivity.
[0104] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0105] Example 1
[0106] (1) Solution preparation: 100 g of copper sulfate pentahydrate and 54 g of disodium ethylenediaminetetraacetate were dissolved in 300 g of water to prepare solution A; 225 g of potassium sodium tartrate was added to 500 g of water and stirred evenly to prepare solution B; 474 g of disodium ethylenediaminetetraacetate and 246 g of ammonium carbonate were dissolved in 3763 g of pure water and stirred evenly to obtain a mixed solution; 63 g of silver nitrate was dissolved in 194 g of pure water, and then added to the mixed solution and stirred thoroughly to prepare solution C.
[0107] (2) Reduction reaction: Solution A and solution B were mixed, 2 g of ethylene glycol was added, and the mixture was heated to 70°C for 2 h to cause a reduction reaction, thereby obtaining solution D.
[0108] (3) pH control: 0.2 g of imidazole, 1 g of oleic acid and a pH adjuster were added to solution D to adjust the pH to 6.0.
[0109] (4) Replacement reaction: In a nitrogen environment, solution C was added dropwise to solution D at a rate of 75 mL / min, while solution D was stirred during the addition, and nitrogen was continuously introduced until the reaction was completed. After the reaction was completed, the reaction solution was filtered, the obtained powder was washed, and vacuum dried in an oven at 50°C for 8 h to obtain silver-coated copper powder. The scanning electron microscope image of the silver-coated copper powder is shown in FIG. Figure 1 shown.
[0110] Example 2
[0111] (1) Solution preparation: 150 g of copper sulfate pentahydrate and 78 g of disodium ethylenediaminetetraacetate were dissolved in 480 g of water to prepare solution A; 338 g of potassium sodium tartrate was added to 800 g of water and stirred evenly to prepare solution B; 956 g of disodium ethylenediaminetetraacetate and 498 g of triethylenetetramine were dissolved in 6020 g of pure water and stirred evenly to obtain a mixed solution; 126 g of silver nitrate was dissolved in 380 g of pure water, and then added to the mixed solution and stirred thoroughly to prepare solution C.
[0112] (2) Reduction reaction: Solution A and solution B were mixed, 3.2 g of butanediol was added, and the mixture was heated to 70° C. for 2 h to cause a reduction reaction, thereby obtaining solution D.
[0113] (3) pH control: 0.4 g of methylthiotetrazolyl, 1.5 g of stearic acid and a pH adjuster were added to solution D to adjust the pH to 5.0.
[0114] (4) Replacement reaction: In a nitrogen environment, silver liquid C was added dropwise to solution D at a rate of 100 mL / min, while solution D was stirred during the addition, and nitrogen was continuously introduced until the reaction was completed. After the reaction was completed, the reaction liquid was filtered, the obtained powder was washed, and vacuum dried in an oven at 50°C for 8 h to obtain silver-coated copper powder. The scanning electron microscope image of the silver-coated copper powder is shown in FIG. Figure 2 shown.
[0115] Example 3
[0116] The difference between Example 3 and Example 1 is that in the reduction reaction of step (2) of Example 3, the crystal form control agent is diethylene glycol, and the addition amount is 3.4 g. The scanning electron microscope image of the silver-coated copper powder is as follows: Figure 3 shown.
[0117] Example 4
[0118] The difference between Example 4 and Example 1 is that in the reduction reaction of step (2) of Example 4, the crystal form control agent is tetraethylene glycol, and the addition amount is 6.2 g. The scanning electron microscope image of the silver-coated copper powder is as follows: Figure 4 shown.
[0119] Example 5
[0120] The difference between Example 5 and Example 1: In the reduction reaction of step (2) of Example 5, the amount of ethylene glycol added is 0.25 g.
[0121] Example 6
[0122] The difference between Example 6 and Example 1: In the reduction reaction of step (2) of Example 6, the amount of ethylene glycol added is 2.5 g.
[0123] Example 7
[0124] The difference between Example 7 and Example 1: In step (3) pH control of Example 7, the inhibitor is thiadiazole, and the added amount is 0.37 g.
[0125] Example 8
[0126] The difference between Example 8 and Example 1: In step (3) pH control of Example 8, the inhibitor is benzimidazole, and the added amount is 0.33 g.
[0127] Example 9
[0128] The difference between Example 9 and Example 1: In step (3) pH control of Example 9, the amount of imidazole added is 0.14 g.
[0129] Example 10
[0130] The difference between Example 10 and Example 1: In step (3) pH control of Example 10, the amount of imidazole added is 0.27 g.
[0131] Comparative Example 1
[0132] (1) Solution preparation: 100 g of copper sulfate and 54 g of disodium ethylenediaminetetraacetate were dissolved in 300 g of water to prepare solution A; 225 g of potassium sodium tartrate was added to 500 g of water and stirred evenly to prepare solution B; 474 g of disodium ethylenediaminetetraacetate and 246 g of ammonium carbonate were dissolved in 3763 g of pure water and stirred evenly to obtain a mixed solution; 63 g of silver nitrate was dissolved in 194 g of pure water and added to the mixed solution and stirred well to prepare solution C.
[0133] (2) Reduction reaction: Solution A and solution B were mixed, and 2 g of ethylene glycol was added. The mixture was heated to 70° C. for a reduction reaction. The reaction time was 2 h, and solution D was obtained.
[0134] (3) Replacement reaction: In a nitrogen environment, solution C was added dropwise to solution D at a rate of 75 mL / min, while solution D was stirred, and nitrogen was continuously introduced until the reaction was completed. After the reaction was completed, the reaction solution was filtered, the obtained powder was washed, and vacuum dried in an oven at 50°C for 8 h to obtain silver-coated copper powder. The scanning electron microscope image of the silver-coated copper powder is shown in FIG. Figure 5 shown.
[0135] Comparative Example 2
[0136] (1) Solution preparation: 100 g of copper sulfate and 54 g of disodium ethylenediaminetetraacetate were dissolved in 300 g of water to prepare solution A; 225 g of potassium sodium tartrate was added to 500 g of water and stirred evenly to prepare solution B; 474 g of disodium ethylenediaminetetraacetate and 246 g of ammonium carbonate were dissolved in 3763 g of pure water and stirred evenly to obtain a mixed solution; 63 g of silver nitrate was dissolved in 194 g of pure water and added to the mixed solution and stirred well to prepare solution C.
[0137] (2) Reduction reaction: Solution A and solution B were mixed, and 0.2 g of ethylene glycol was added. The mixture was heated to 70° C. for a reduction reaction. The reaction time was 2 h, and solution D was obtained.
[0138] (3) pH control: 0.2 g of imidazole, 1 g of oleic acid and a pH adjuster were added to solution D to adjust the pH to 7.0.
[0139] (4) Replacement reaction: In a nitrogen environment, pour solution C into solution D, stir solution D while adding dropwise, and keep nitrogen flowing until the reaction is completed. After the reaction is completed, filter the reaction solution, wash the obtained powder, and vacuum dry it in an oven at 50°C for 8 hours to obtain silver-coated copper powder. The scanning electron microscope image of the silver-coated copper powder is shown in Figure 2. Figure 6 shown.
[0140] Comparative Example 3
[0141] (1) Solution preparation: 100 g of copper nitrate and 54 g of disodium ethylenediaminetetraacetate were dissolved in 300 g of water to prepare solution A; 225 g of potassium sodium tartrate was added to 500 g of water and stirred evenly to prepare solution B; 474 g of disodium ethylenediaminetetraacetate and 246 g of ammonium carbonate were dissolved in 3763 g of pure water and stirred evenly to obtain a mixed solution; 63 g of silver nitrate was dissolved in 194 g of pure water and added to the mixed solution and stirred well to prepare solution C.
[0142] (2) Reduction reaction: Solution A and solution B were mixed and heated to 70°C for 2 h to undergo a reduction reaction, thereby obtaining solution D.
[0143] (3) pH control: 0.2 g of imidazole, 1 g of oleic acid and a pH adjuster were added to solution D to adjust the pH to 6.0.
[0144] (4) Replacement reaction: In a nitrogen environment, solution C was added dropwise to solution D at a rate of 75 mL / min, while solution D was stirred during the addition, and nitrogen was continuously introduced until the reaction was completed. After the reaction was completed, the reaction solution was filtered, the obtained powder was washed, and vacuum dried in an oven at 50°C for 8 h to obtain silver-coated copper powder. The scanning electron microscope image of the silver-coated copper powder is shown in FIG. Figure 7 shown.
[0145] Silver-coated copper powder performance test
[0146] 1. Test Method
[0147] 1. Particle size analyzer test:
[0148] The particle size D10, D50 and D100 of the silver-coated copper powder were tested using a laser particle size analyzer.
[0149] 2. Specific surface area tester test:
[0150] The BET specific surface area of silver-coated copper powder was tested using a specific surface area tester.
[0151] 3. Thermogravimetric analysis (TG) test:
[0152] The TG value of silver-coated copper powder was tested using a thermogravimetric analyzer.
[0153] 4. Line resistivity and contact resistivity test:
[0154] According to the mass percentage of epoxy resin 2.6%, hexahydrophthalic acid diglycidyl ester 0.8%, dodecenyl succinic anhydride 0.1%, solvent 3.5% (including butyl carbeta acetate 2.3%, pine alcohol 1.2%), nano silver powder 21.75% (average particle size of 300nm), silver-coated copper powder prepared in the embodiment and comparative example 71.25%, weigh the raw materials, mix them evenly, and use a three-roll grinder to roll the slurry 8 times, and make the fineness less than 5μm, to prepare silver-coated copper powder heterojunction battery slurry, and test the slurry viscosity. After screen printing, cure at 170℃ for 5min, sinter at 200℃ for 10min, and test the 20μm opening line resistivity and 20μm opening contact resistivity.
[0155] 2. Test Results
[0156] The performance test results of the silver-coated copper powder of each embodiment and comparative example are shown in Table 1.
[0157] Table 1 Performance test results of silver-coated copper powder in various embodiments and comparative examples
[0158]
[0159] From Table 1 and Figure 1-7 It can be seen that the silver-coated copper powder of the embodiment is a uniformly coated polyhedron, with uniform particle size, narrow particle size distribution, and regular particle shape, while the silver-coated copper powder of the comparative example has poor consistency in particle size, and there are depressions and damage on the particle surface. The percentage of the TG value of the silver-coated copper powder of the embodiment at 300°C is less than that of the comparative example, indicating that it has good thermal stability within this temperature range. The line resistivity and contact resistivity of the embodiment are both less than those of the comparative example, indicating that its conductive performance is better. Therefore, it is shown that the preparation method of the present invention can effectively improve the coating uniformity and particle size consistency of the silver-coated copper powder, thereby improving the conductive performance.
[0160] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0161] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing silver-coated copper powder, characterized in that: The following steps are involved: Prepare solution A, solution B and solution C; the solution A comprises copper salt and complexing agent I, the solution B comprises a reducing agent, and the solution C comprises silver salt, complexing agent I and complexing agent II; The solution A and the solution B are mixed, and a crystal form control agent is added to perform a reduction reaction to obtain a solution D; adding an inhibitor and a carboxylic acid to the solution D; The solution C is added dropwise to the solution D to carry out a replacement reaction, thereby obtaining silver-coated copper powder.
2. The preparation method according to claim 1, characterized in that: The solution A satisfies at least one of the following: (A) the copper salt comprises at least one of copper nitrate and copper sulfate; (B) The complexing agent I includes at least one of ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid salt, and thiosulfate.
3. The preparation method according to claim 1, characterized in that: The solution B satisfies at least one of the following: (a) the reducing agent comprises at least one of ascorbic acid, hydrazine hydrate, glucose and potassium sodium tartrate; (b) The pH range of the solution B is 5-7.
4. The preparation method according to claim 1, characterized in that: The solution C satisfies at least one of the following: (1) The silver salt comprises at least one of silver nitrate and silver sulfate; (2) the complexing agent II comprises at least one of ammonium carbonate, ammonium bicarbonate, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and ammonia water; (3) The pH range of the solution C is 5 to 7.
5. The preparation method according to claim 1, characterized in that: The crystal form control agent satisfies at least one of the following: (i) the crystal form controlling agent comprises at least one of ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, and tetraethylene glycol; (ii) The molar ratio of the crystal form controlling agent to the copper salt in the solution A is (0.01-0.1):
1.
6. The preparation method according to claim 1, characterized in that: The adding of the inhibitor and the carboxylic acid to the solution D satisfies at least one of the following: (I) the inhibitor comprises at least one of imidazole, benzimidazole, thiazole, benzothiazole, 1,2,3-triazole, 1,2,4-triazole, thiadiazole and methylmercaptotetrazole; (II) the molar ratio of the inhibitor to the copper salt is (0.005-0.01):1; (III) The molar ratio of the inhibitor to the carboxylic acid is 1:
1.
7. The preparation method according to claim 1 or 6, characterized in that: The carboxylic acid includes organic substances containing a carboxylic acid group.
8. The preparation method according to claim 1, characterized in that: The replacement reaction satisfies at least one of the following: (1) The dropwise addition rate of the solution C is 50 to 100 mL / min; (2) The pH range of the solution D is 5 to 7.
9. The preparation method according to claim 1 or 8, characterized in that: After the replacement reaction is completed, a drying process is further performed; the drying process is performed at a temperature of 20 to 50° C. and for a time of 8 to 12 hours.
10. A silver-coated copper powder, characterized in that: The silver-coated copper powder comprises the silver-coated copper powder obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for uniformly and compactly coating silver shell layer on surface of copper particle and alloying
CN118404056A